Stay-green trait improves yield, quality, and feeding value of forage oats under contrasting eco-sowing systems - Duan, Huimin; Wu, Rui; Wang, Wenhu; Zhang, Ruifang; Hu, Zelong; Liang, Guoling; Liu, Wenhui (Frontiers in Plant Science, 2026)
IntroductionOat (Avena sativa L.) is an important food and forage crop whose yield and quality are influenced by genotype, environmental conditions, and sowing regimes. The stay-green (SG) trait, which delays leaf senescence and maintains photosynthetic capacity, can enhance yield and forage quality; however, systematic evaluation in oat remains limited.MethodsTwo genotypes—QINGYAN 3 (control, CK) and its stay-green mutant (SG)—were evaluated over two consecutive years (2023–2024) at Huangzhong, Qinghai and Yuanmou, Yunnan under contrasting eco-sowing conditions. The SG mutant was developed through field-based phenotypic selection and long-term cultivation, resulting in a stable trait. Yield, nutritional composition, forage value, and stability were evaluated. Genotype, environment, and sowing regime effects were analyzed using linear mixed models (LMM), the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS), and the Analytic Hierarchy Process (AHP) .ResultsThe SG genotype showed significantly higher biomass, grain yield, starch, protein, and fat contents than CK. It also had lower fiber fractions (ADF and NDF) and higher digestibility indicators, including dry matter intake (DMI), digestible dry matter (DDM), total digestible nutrients (TDN), relative feed value (RFV), and relative forage quality (RFQ). Environmental and inter-annual effects were pronounced: warm, low-latitude conditions favored higher yield, while cool, high-altitude conditions enhanced nutritional composition and forage quality.ConclusionOverall, the SG genotype outperformed CK in both yield and quality, while CK exhibited slightly greater stability across environments. The SG trait combines high yield with superior quality, providing valuable germplasm for oat improvement. Selecting genotypes according to ecological zones can further enhance forage yield and quality, supporting sustainable livestock production.